Development and Reliability of Technical-Tactical and Time-Motion Real-Time Analysis in the World Taekwondo Grand Prix [Rozwój I Wiarygodność Analizy Techniczno-Taktycznej I Czasowo-Ruchowej W Czasie Rzeczywistym W World Taekwondo Grand Prix] - Aedo-Munoz, E (Idokan Poland Association, 2021)
Background. Despite its importance, time-motion and technical-tactical analyses are rarely applied in Taekwondo by coaches and in technical assistance because of the lack of technical-tactical protocols for real-time analysis. Problem and aim. This study aimed to elaborate and validate a new technical-tactical protocol in Taekwondo for real-time analysis, as well as to demonstrate the characterization and practical application of the app for general models of high-level championships. Methods. The data was constructed for 7,370 sequential technical-tactical actions - a total of 189 rounds - which were observed during 64 matches. From this number, twenty-four matches from a total of 64 (37.5%), were analyzed twice by one expert with a 24hour interval between them and once by another expert. Frequencies and time (seconds) of the technical-tactical variables selected for the analysis correspond to the following groups: a) Positioning; b) Techniques; c) Clinch; and d) Pause. The Mann-Whitney comparison and Cohen s Kappa coefficient were used, p>0.05. Results. Similar technical-tactical real-time analyses were observed with no significant inter-rater difference in the attack or counterattack variables (P=0.959), in stance variables (P=1.0) or pause time (P=0.959), with agreement between 0.49 (moderate) and 0.75 (strong). There were also no significant intra-rater differences in the attack and counterattack variables (P=1.0), in stance variables (P=1.0) or pause time (P=1.0), with agreement between 0.72 (strong) and 0.87 (almost perfect). Tactical analysis reveals that athletes were more effective in scoring defensive actions than offensive, scoring the most times with 1-point techniques; bandal chagui was the technique with the highest frequency of scoring and ~20% of the scoring came from penalties. Conclusion. These results represent an advantage, as coaches can use this protocol, showing immediate feedback to your athlete during competitions or training, as the App can be installed on tablets and smartphones. © 2021 Idōkan Poland Association. All Rights Reserved.